Honduras Public Expenditure Review : Towards Restoring Fiscal Consolidation - World Bank (Washington, DC, 2014)
Fiscal consolidation remains the central challenge facing Honduras, mainly due to increasing current expenditures. The widening fiscal deficit has been driven by a significant increase in current expenditures. These increased current expenditures, which add rigidity to the budget, have occurred at the expense of investments. The efficiency of spending remains a key constraint. Limited improvements, especially in health and education outcomes despite high allocations to these sectors, suggest the need to improve the efficiency and quality of expenditures. Increased public expenditures have not delivered in terms of growth and improved public services, and whether the country is ready for decentralization remains an open question. Growing fiscal deficits and weak public financial management practices have constrained the ability of the central government to implement and finance the decentralization process. Current decentralization targets would pose significant fiscal challenges to the central government. The deterioration of the fiscal deficit is not a result of fiscal decentralization. However, further decentralization efforts could pose significant fiscal challenges to the central government.